ISLAMIC CAPITAL MARKET VOLATILITY: RESILIENCE OF SHARIA STOCK INDEX AMID RISING GLOBAL UNCERTAINTY - Sutikno, Johan Dwi; Rizkyaningrum, Adinda Agustinayu; Asiyah, Binti Nur (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
This study examines stock price dynamics amid increasing global economic uncertainty, compounded by geopolitical conflicts, bank interest rate policies, the pandemic, and financial crises, which have had a serious impact on the stability of a country's economy. In this context, the Islamic capital market has emerged as an alternative investment offering a safe haven amid global economic uncertainty. This study aims to analyze how global economic uncertainty affects stock price fluctuations in the Islamic capital market in ASEAN countries, as seen from the growth of the Islamic stock index. This study uses a qualitative approach based on a review of literature and empirical data. The results indicate that Islamic stocks can be affected by global economic uncertainty but are more resilient to external or internal factors related to usury, gambling, and uncertainty. Despite facing pressure from global market fluctuations, Islamic stocks still demonstrate growth potential, particularly in ASEAN countries with majority Muslim populations. The results of this study are expected to provide investors with insights for planning investment strategies as hedging instruments in accordance with sharia principles, while considering global economic conditions and a country's macroeconomy.